Navigating currency crises: how developed nations ensure liquidity and what Indonesia can learn? The role of Islamic finance - Mohd Thas Thaker, Hassanudin; Ah Mand, Abdollah; Hosen, Mosharrof; Qoyum, Abdul (Al Qasimia University, 2025)
This study critically examines the dynamics of currency liquidity across developed economies during the 2001 and 2009 financial crises and the COVID-19 pandemic, assessing the efficacy of policy responses in mitigating economic disruptions. By employing Welch’s unequal variancet-test, Variable Lag Granger Causality (VLGC), Variable Lag Transfer Entropy (VLTE), and time-frequency coherence analysis, we uncover significant disparities in liquidity conditions, revealing that currency liquidity during the COVID-19 crisis surpassed that of prior financial crises. Our findings further expose nonlinear causal relationships between monetary policy indices and currency liquidity, with short-term COVID-19 effects exerting a more pronounced influence than long-term impacts. Beyond diagnostic analysis, this study challenges conventional crisis response frameworks by introducing Islamic finance as a viable policy alternative for emerging economies, particularly Indonesia. We argue that Islamic financial mechanisms—rooted in risk-sharing and asset-backed principles—can enhance aggregate demand and stabilize exchange rates during systemic shocks. As the first comparative analysis of exchange rate behavior across health and financial crises involving the USD, GBP, and JPY, this research fills a critical gap in the literature while offering actionable policy prescriptions for ASEAN economies. Our results compel a reevaluation of crisis management blueprints, emphasizing the need for adaptive monetary strategies and the underutilized potential of Islamic finance in fostering economic resilience. This study not only advances theoretical discourse but also provides policymakers with empirically grounded strategies to fortify financial systems against future disruptions.